2023
DOI: 10.1111/camh.12637
|View full text |Cite
|
Sign up to set email alerts
|

Short Research Article: Changes in life functioning in a self‐help, online program for child and adolescent anxiety

Abstract: BackgroundAnxiety‐related functional impairment, as reflected by life interference, is a lesser explored but highly relevant treatment outcome, and it is crucial that it be included and examined in the evaluation of treatment outcomes of internet‐delivered Cognitive Behavioural Therapy (iCBT).MethodsThis single group, pre‐post study examined changes in life interference and anxiety symptoms in a sample of children (n = 1198; mean age 9.66 years) and adolescents (n = 721; mean age 13.66 years) participating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Politte-Corn and colleagues evaluated age-related differences in social media use, online social support and depressive symptoms in adolescents and emerging adults (Politte-Corn, Nick, & Kujawa, 2023). As another example, in the article by Rowe et al (2023) evaluating the use of a self-help online programme for children and adolescents, reductions in life interference were observed in children but not in adolescents. Other factors, such as the severity of symptoms, also seem to have an impact on the efficacy of the interventions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Politte-Corn and colleagues evaluated age-related differences in social media use, online social support and depressive symptoms in adolescents and emerging adults (Politte-Corn, Nick, & Kujawa, 2023). As another example, in the article by Rowe et al (2023) evaluating the use of a self-help online programme for children and adolescents, reductions in life interference were observed in children but not in adolescents. Other factors, such as the severity of symptoms, also seem to have an impact on the efficacy of the interventions.…”
mentioning
confidence: 99%
“…A pilot randomized clinical trial found that a guided paced breathing audiovisual intervention of no more than 10 min per session decreased anxiety symptoms in the intervention group compared to the control group (Shank et al., 2022). Another study evaluating a self‐help, online programme showed improvements in anxiety symptoms in children and adolescents, and reductions in life interference in children (Rowe, Evans, Donovan, Spence, & March, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation